METODE PENUGASAN DALAM PEMBELAJARAN PAI - Ismail, Moh; Hadi, M. Noer; Sunaiyah, Salma (Institut Agama Islam Negeri Kediri, 2017)
Abstract: Based on the results obtained a conclusion that Assignment Method Class XII PAI included in the category enough. It is based on the acquisition of real score with the average value (Mean) are 130.86. While the student's motivation is also in fair category based on the acquisition value of the average (mean) of 116.55. Based on calculations of influence, it can be deduced that there is a strong and significant influence between the Assignment Method on the students motivation in class XII PAI. The magnitude of the influence coefficient is 0.616, while the result obtained significant effect of value amount 10.2858. The value is more than equal to 1.654 at 5 percent error rate. While the determination coefficient test result 0,37,94. this means that 37.94 percent of the Assignment Method affect class XII student motivation on the subjects of Islamic Religious Education. Abstrak: Berdasarkan hasil penelitian diperoleh suatu kesimpulan bahwa Metode PenugasanPAI termasuk dalam kategori cukup. Hal ini berdasarkan perolehan real score dengan nilai rata-rata (Mean) sebasar 130,86. Sedangkan motivasi belajar siswa juga dalam kategori cukup berdasarkan perolehan nilai rata-rata (mean) sebesar 116,55. Berdasarkan hasil perhitungan pengaruh, dapat ditarik kesimpulan bahwa terdapat pengaruh yang kuat dan signifikan antara Metode Penugasan terhadap motivasi belajar siswa pada mata pelajaran PAI. Besarnya koefisien pengaruh adalah 0,616, sedangkan hasil signifikansi pengaruh didapatkan nilai thitung sama dengan 10,2858. nilai tersebut lebih besar dari ttabel sama dengan 1,654 pada tingkat kesalahan 5 persen. Sedangkan pada pengujian koefisien determinasi diperoleh hasil 0,37,94. hal ini berarti bahwa sebesar 37,94 persen Metode Penugasan mempengaruhi motivasi belajar siswa kelas XII pada mata pelajaran Pendidikan Agama Islam.